Coexistence of a ruptured ectopic pregnancy and cervical cancer: how to avoid a diagnostic error when the same symptoms present two different diagnoses - Kaźmierczak, Kamila; Cholewiński, Witold; Nowakowski, Błażej (Contemporary Oncology/Współczesna Onkologia, 2021)
An ectopic pregnancy occurs in approximately 0.5–2% of all pregnancies. The number of cases of cervical cancer in women under 30 years of age in Poland is less than 100 cases per year. The case presented herein concerns a rare clinical situation of a 29-year-old woman admitted to the Gynaecological Oncology Department with a diagnosis of cervical cancer. The main symptom resulting in the patient’s referral was ascites. The presence of free fluid in the peritoneal cavity in patients diagnosed with a malignant tumour suggests a high degree of progression of the underlying disease, though this could not be confirmed in a clinical study in this case. An interview, examination, and laboratory tests confirmed a coexisting life-threatening ruptured tubal pregnancy. The consequences of not recognising both an ectopic pregnancy and cervical cancer in a patient presenting with nonspecific clinical symptoms could pose a serious threat to health and life.